MUTATIONS AND DRUG RESISTANCE IN MALARIA, TOXOPLASMOSIS AND GIARDIASIS: A REVIEW OF CURRENT CHALLENGES AND MECHANISMS - Mohammed, Othman M; Noori, Saif Subhi; Salam, Ibrahim (Journal of Medical Genetics and Clinical Biology, 2024)
This study addresses the growing threat of drug resistance in malaria, toxoplasmosis, and giardiasis by analyzing the underlying genetic mutations that compromise the efficacy of current treatments. Understanding these mechanisms is crucial for developing more effective therapeutic strategies. A comprehensive review of literature was conducted to identify key mutations associated with drug resistance. In malaria, the focus was on mutations in genes like Pfmdr1, Pfcrt, Pfmrp, and Pfnhe1, which are linked to resistance against antimalarials, particularly the K76T mutation in PfCRT for chloroquine resistance. For toxoplasmosis, mutations in the DHFR-TS and DHPS genes were analyzed, particularly the T83N mutation in DHFR-TS, which confers resistance to pyrimethamine. In giardiasis, the study reviewed mutations in the ferredoxin oxidoreductase gene that reduce the efficacy of metronidazole. The analysis revealed that specific mutations in these parasites significantly contribute to the development of drug resistance, complicating treatment protocols. In malaria, PfMRP1 mutations are particularly concerning due to their role in resistance to both chloroquine and quinine. Toxoplasmosis resistance is notably influenced by DHFR-TS and DHPS mutations, while giardiasis resistance is linked to alterations in drug transport and enzyme function. This study synthesizes the most recent findings on genetic resistance mechanisms in these three parasitic diseases, offering insights that could inform the development of next-generation therapies and improve resistance management strategies, ultimately contributing to better health outcomes.